PROBLEMS IN INCREASING THE INVESTMENT ACTIVITY OF COMMERCIAL BANKS IN THE STOCK MARKET IN OUR COUNTRY (E Global Congress, 2025)
Today, increasing investment activity through the development of the securities market is one of the important tasks for the economies of many countries, but in this process a number of problems and obstacles may be encountered. It is advisable to study and analyze ways to comprehensively assess investment activity, establish a system to eliminate various existing problems associated with the growth of investment activity due to the development of the securities market in our country: